Analisis Determinan PAD: Belanja Modal, Mandiri Fiskal, Tingkat Kemiskinan dan PDRB per Kapita - Abid Laksa Linuwih; Andryan Setyadharma (ARBITRASE: Journal of Economics and Accounting, 2025)
This study aims to analyze the determinants of Regional Original Revenue (PAD) in seven districts/cities in the Solo Raya region during the 2014–2023 period. The independent variables in this study include the Capital Expenditure Ratio, Fiscal Independence Ratio, Poverty Rate, and Gross Regional Domestic Product (GRDP) per capita. A quantitative approach with panel data regression was applied using the Fixed Effects Model, selected based on Chow and Hausman tests. To address the heteroscedasticity issue, the Generalized Least Squares (GLS) method with a panel EGLS approach was employed. The estimation results show that the Capital Expenditure Ratio, Fiscal Independence Ratio, and GRDP per capita have a positive and significant effect on PAD, while the Poverty Rate has no significant effect. The coefficient of determination of 91.93 percent indicates that the model has a very strong explanatory power. These findings suggest that efforts to increase PAD should focus on effective infrastructure development, strengthening fiscal independence, and enhancing regional economic capacity. This research is expected to serve as a reference for local governments in formulating data-driven and region-specific fiscal strategies.